The relationship of bullying to empathy and basic psychological needs: from the students’ point of views and how teachers handle it (Training and Practice : Journal of Educational Sciences, 2018)
In our thesis we wrote about bullying from the students’ and the teachers’ points of view. This phenomenon can be reached from several aspects, in our survey we are studying its connection with empathy and basic psychological needs among students and teachers. During our research questionnaries concerning empathy skills and basic psychological needs were filled in by 102 secondary school students and 40 teachers. Besides these, students filled in a list of queries about to what extent they are concerned about bullying, while teachers were asked to fill in a questionnaire about handling bullying.Bullying manner is associated with weaker empathy skills, while students suffering from bullying showed more unflattering values related to basic psychological needs. Concerning the teachers’ attitude towards school bullying it was found that their empathy skills and the level their basic psychological needs are satisfied correlated with how seriously they would take bullying.